2023
DOI: 10.1037/ppm0000361
|View full text |Cite
|
Sign up to set email alerts
|

Solving the puzzle of null violent media effects.

Abstract: Over the past half-century, many professional and scientific organizations have issued statements about the harmful effects of violent media on children and adolescents. Most pediatricians, media researchers, and parents also believe that violent media can be harmful. Although most studies report significant violent media effects, some report null effects. In this article, we address the puzzle of why some studies obtain null effects. Some possible factors include the use of inappropriate or excessive number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 77 publications
(103 reference statements)
1
31
0
Order By: Relevance
“…The reviews from major scientific organizations and meta-analyses from most media violence scholars remain consistent in reporting a significant relationship between media violence exposure and aggression; however, disagreement remains among some scholars over the interpretation of the results of such reviews (Ferguson et al, 2020). It is clear that more research into this relationship is needed to help clarify the conflicting data, perhaps by identifying characteristics that are unique to replication failures (Bushman & Anderson, 2021; Kim et al, 2021).…”
Section: Lack Of Consistency In Media Violence Effects In Texas Samplesmentioning
confidence: 99%
“…The reviews from major scientific organizations and meta-analyses from most media violence scholars remain consistent in reporting a significant relationship between media violence exposure and aggression; however, disagreement remains among some scholars over the interpretation of the results of such reviews (Ferguson et al, 2020). It is clear that more research into this relationship is needed to help clarify the conflicting data, perhaps by identifying characteristics that are unique to replication failures (Bushman & Anderson, 2021; Kim et al, 2021).…”
Section: Lack Of Consistency In Media Violence Effects In Texas Samplesmentioning
confidence: 99%
“…Our approach in these studies may also contribute to the body of work on media effects. Recent work on media effects has led to some debate on when, how, and if television and other forms of media actually influence viewers’ beliefs and behavior (Bushman & Anderson, 2021; Coyne et al, 2019; Ferguson, 2015; Ferguson et al, 2017). In our studies, we documented a roughly medium-sized effect of media on intersubjective norms, but not personal beliefs.…”
Section: Theoretical and Methodological Implicationsmentioning
confidence: 99%
“…We tested these hypotheses in the context of media effects, where there remains debate about if and how media content influences children and adults (Bushman & Anderson, 2021; Coyne et al, 2019; Ferguson, 2015; Ferguson et al, 2017). In Study 1, we quantified the extent to which U.S. children’s TV programming includes a nonverbal bias.…”
Section: Intersubjective Norms and Nonverbal Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, some studies have shown that gaming violence is not an antecedent of aggressive behavior (Drummond et al, 2020; Ferguson, 2007; Ferguson et al, 2008; Kuhn et al, 2019). Nevertheless, the technical report of the American Psychological Association task force on violent media and numerous theories supported that violent video game use is a risk factor for adverse outcomes (APA, 2015; Bushman & Anderson, 2021). Of course, as Gotz et al (2021) note, psychological phenomena are most likely determined by a multitude of causes.…”
Section: Introductionmentioning
confidence: 99%